Effect of Esketamine Compared with Sufentanil Combined with Propofol in Patients Undergoing First Trimester Surgical Abortion: A Randomized, Double-Blinded Clinical Trial - Guan Y; Wang H; Cong X; Zhang B; Lin Y; Wang X (Drug Design, Development and Therapy)
Yingchao Guan,1 Haochen Wang,1,2 Xiaojing Cong,1,2 Beibei Zhang,1 Yusong Lin,1,2 Xiaodong Wang1,2 1Department of Anesthesiology, Weihai Municipal Hospital, Cheeloo College of Medicine, Shandong University, Weihai City, Shandong Province, People’s Republic of China; 2The Second School of Clinical Medicine of Binzhou Medical University, Yantai City, Shandong Province, People’s Republic of ChinaCorrespondence: Xiaodong Wang, Department of Anesthesiology, Weihai Municipal Hospital, Cheeloo College of Medicine, Shandong University, and The Second School of Clinical Medicine of Binzhou Medical University, No. 70 heping Road, Huancui District, Weihai City, Shandong, People’s Republic of China, Tel +86-13508914062, Email wxd1982819@126.comBackground: We explored whether esketamine anesthesia during first-trimester surgical abortion can reduce intraoperative hemodynamic fluctuations and improve patients’ respiratory function.Methods: A total of 197 patients who underwent a first-trimester surgical abortion were included in the analysis. Patients were randomly assigned to either the esketamine anesthesia group (group E, n=98) or sufentanil anesthesia group (group S, n=99). The primary outcomes were systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MBP), heart rate (HR), respiratory rate (RR) and end-tidal carbon dioxide partial pressure (PetCO2) during the surgery. Secondary outcomes included body movement, apnea, hypoxemia, postoperative nausea and vomiting (PONV), dizziness, anesthesia recovery time, Richmond Agitation and Sedation Scale (RASS) score, and postoperative pain.Results: Patients in Group E had a more stable intraoperative SBP (p=0.001), DBP (p=0.014), MBP (p=0.003), and HR (p=0.001). There was no significant difference in intraoperative RR between the two groups (p=0.108); however, PetCO2 in group E remained at preoperative levels, whereas it increased in group S during surgery (p< 0.001). The risk of apnea and hypoxemia in group E was lower (RR 0.32, 95% CI [0.13, 0.76], p=0.006; RR 0.13, 95% CI [0.03, 0.54], p=0.001). The incidence of intraoperative body movement (50% vs 27%, p=0.003), postoperative dizziness (45% vs 30%, p=0.024), and nausea (7% vs 0%, p=0.007) was higher in group E. There were no differences in anesthesia recovery time, postoperative RASS score, pain, or vomiting.Conclusion: Compared with sufentanil, esketamine anesthesia during the first trimester surgical abortion can maintain stable intraoperative hemodynamics and respiratory function during surgery and reduce apnea and hypoxemia. Esketamine may increase the risk of dizziness and PONV after surgical abortion.Plain Language Summary: Induced abortion is a simple and common health care procedure. The combination of sedative drugs and anesthesia is currently the main anesthetic regimen for abortion. However, the choice of analgesic drug remains controversial. Esketamine is a promising alternative that has been widely used in painless treatment. However, reports on the use of esketamine in abortion surgery are insufficient, and its effectiveness and adverse reactions require further in-depth and comprehensive exploration. Therefore, we designed this prospective randomized controlled trial. We found that compared to sufentanil, esketamine anesthesia during first-trimester surgical abortion could maintain stable intraoperative hemodynamics and respiratory function during surgery and reduce apnea and hypoxemia, but might increase the risk of dizziness and PONV.Keywords: esketamine, hemodynamics, respiration, abortion, randomized clinical trial